Bioconjugation strategies to couple supramolecular exo-functionalized palladium cages to peptides for biomedical applications. Issue 8 (12th January 2017) - Han, J.; Schmidt, A.; Zhang, T.; Permentier, H.; Groothuis, G. M. M.; Bischoff, R.; Kühn, F. E.; Horvatovich, P.; Casini, A.
Abstract : Supramolecular metallacages hold promise for targeted drug delivery. Abstract : Supramolecular Pd2 L4 cages (L = ligand) hold promise as drug delivery systems. With the idea of achieving targeted delivery of the metallacages to tumor cells, the bioconjugation of exo -functionalized self-assembled Pd2 L4 cages to peptides following two different approaches is reported for the first time. The obtained bioconjugates were analyzed and identified by high-resolution mass spectrometry.